Personal Branding Content Creator Warung Madura akun Tiktok @ainimufarrihah - Agustin, Fabela Dian; Poernamasari, Nadya (Jurnal Pustaka Komunikasi, 2025)
research focuses on how Personal Branding is applied by a Warung Madura Content Creator on the Tiktok application, focusing on the @ainimufarrihah account. Personal Branding is a process of individual activity to build a positive image in the eyes of the audience. This study aims to explore the Personal Branding applied by @ainimufarrihah in building and maintaining her Personal Branding on the Tiktok application. This research uses a qualitative content analysis approach. The analysis was carried out using Peter Montoya's personal branding aspects. The data collection techniques used are interviews, observation, documentation, and literature study. And the data analysis technique used is Krippendorff's content analysis model, to test the validity of the data in this study using source triangulation techniques. The concept of forming Personal Branding on the @ainimufarrihah account includes everything, but there are some that dominate the most, namely, specialisation, leadership, difference, constancy and good name.  So for other indicators such as personality, appearance, unity are not included in the majority. The findings of this research can provide insight into the effectiveness of applying a consistent branding concept related to increasing visibility and promotional contributions with the existence of Madurese grocery stores on social media can have an effect on the future in order to always keep up with the times in maintaining sales stability.